2020
DOI: 10.21203/rs.3.rs-39240/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Who Indicates Caesarean Section in Romania? A Cross-Sectional Survey in Tertiary Level Maternity on Childbirth Patients and Doctors' Profiles

Abstract: Abstract Background. C-section rate in Romania is the second-highest in the European Union (44.1% in 2017) and the number of C-sections performed in the country increased by 32.1% between 2009 and 2017. We offer for the first time insights into the practice and perceptions of patients and doctors in Romania towards delivery mode and on health system particularities that lead to increased numbers of C-sections. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This may also have affected results; however, in which direction cannot be predicted. According to previous data, older mothers access health services more frequently 2 and may have higher risks of cesarean 4 ; however, their expectation of QMNC may also be higher. In view of these limitations, we cannot extrapolate the results to the entire population of mothers.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This may also have affected results; however, in which direction cannot be predicted. According to previous data, older mothers access health services more frequently 2 and may have higher risks of cesarean 4 ; however, their expectation of QMNC may also be higher. In view of these limitations, we cannot extrapolate the results to the entire population of mothers.…”
Section: Discussionmentioning
confidence: 94%
“…According to recent estimates, the cesarean rate in Romania is increasing significantly, with 37.1% of total births occurring by cesarean in 2016 2 ; this frequency reaches more than 80% in private clinics. 3 Several factors may be contributing to this high average rate of cesarean in Romania: few centers provide prenatal parental education, relatively high number of births in private clinics, low number of midwives, limited autonomy of midwives in the clinical decision process, women's preferences, 4 and increasing maternal age. 5,6 Although reducing the cesarean rate is recognized as a national priority, some of the current regulations (e.g., reimbursing hospitals with higher rates of cesarean compared with spontaneous vaginal birth [SVB]) may actually be a serious barrier to reducing the cesarean rate in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that an increased rate of caesarean section has been observed at the national level, which has been increasing in recent years, unrelated to the COVID-19 pandemic. In 2012, the rate of caesarean sections at the national level was 41.2% of all births, and in 2017, Romania was ranked second in Europe after Cyprus regarding this rate [ 42 , 43 ]. This high rate is mainly due to the desire of women, most caesarean sections being on request without an obstetric indication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of 117 singleton pregnant women who gave birth at term, most unplanned CSs were attended by specialists whereas most vaginal births were attended by resident doctors. 7 Another research showed that less than 1% of women who gave birth in a tertiary maternity hospital between 2014 and 2020 delivered vaginally after having a caesarean delivery. 8 The latter means that virtually all women who gave birth by CS had a subsequent CS for their following pregnancy, contributing to the high rate of CS deliveries in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…The few small studies conducted in Romania on this topic suggest that there are health system particularities that might favour CS deliveries. For example, in a study of 117 singleton pregnant women who gave birth at term, most unplanned CSs were attended by specialists whereas most vaginal births were attended by resident doctors 7 . Another research showed that less than 1% of women who gave birth in a tertiary maternity hospital between 2014 and 2020 delivered vaginally after having a caesarean delivery 8 .…”
Section: Introductionmentioning
confidence: 99%